2009
DOI: 10.1002/pon.1511
|View full text |Cite
|
Sign up to set email alerts
|

Cancer patients' decisions about discussing Internet information with their doctors

Abstract: Many factors influence cancer patients' and caregivers' decisions about discussing Internet information with their doctors. The coherence of the reasons across the communities in this study and in other studies suggests that this typology of reasons is both thorough and valid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 21 publications
2
33
0
2
Order By: Relevance
“…Az in formált beteg aktívabb a döntéshozatalban [28], és a döntéshozatalban aktív beteg kevésbé hibáztatja az or vost, ha nem elégedett a folyamatok kimenetelével. Egy ausztrál kutatás arról számol be, hogy azon orvosok szá mára, akik pozitívan viszonyulnak az internethasználó beteghez, megkönnyebbülést jelent, ha a felelősséget megoszthatják vele [29].…”
Section: Döntési Mechanizmusokunclassified
“…Az in formált beteg aktívabb a döntéshozatalban [28], és a döntéshozatalban aktív beteg kevésbé hibáztatja az or vost, ha nem elégedett a folyamatok kimenetelével. Egy ausztrál kutatás arról számol be, hogy azon orvosok szá mára, akik pozitívan viszonyulnak az internethasználó beteghez, megkönnyebbülést jelent, ha a felelősséget megoszthatják vele [29].…”
Section: Döntési Mechanizmusokunclassified
“…Some empirical studies have examined the association between education and cancer patients’ cancer information seeking and reported positive associations between education and cancer information seeking (e.g., Bylund, Gueguen, D’Agostino, Imes, & Sonet, 2009; Carlsson, 2000). However, most previous studies in this area have used convenience samples of patients from cancer clinics, hospitals or online communities rather than a population-based sample.…”
Section: The Effect Of Education On Cancer Information Seekingmentioning
confidence: 99%
“…Current literature points to increased patient empowerment and engagement due to HRIU. For example, Bylund et al found that sharing online health information has been associated with survivors experiencing higher involvement in decision making, greater satisfaction with treatment choices, improved coping skills, and reduced anxiety [19]. In addition, online health information has been found to empower survivors to discuss information with their providers and meet their psychological needs; and discussions of online health information have been shown to positively affect the patient-provider relationship [19][20][21].…”
Section: Introductionmentioning
confidence: 97%
“…For example, Bylund et al found that sharing online health information has been associated with survivors experiencing higher involvement in decision making, greater satisfaction with treatment choices, improved coping skills, and reduced anxiety [19]. In addition, online health information has been found to empower survivors to discuss information with their providers and meet their psychological needs; and discussions of online health information have been shown to positively affect the patient-provider relationship [19][20][21]. However, one caveat to note is that in spite of these advantages, a survey revealed that 62% of survivors reported sometimes or never discussing Internet information with their healthcare providers [19].…”
Section: Introductionmentioning
confidence: 97%